Stay away or stay together? Social contagion, common identity, and bystanders’ interventions in homophobic bullying episodes - António, R.; Guerra, R.; Moleiro, C. (Group Processes and Intergroup Relations, 2020)
Two studies explored the link between social contagion concerns and assertive bystanders’ behavioral intentions in homophobic bullying episodes. Study 1 (N = 216) examined if adolescents’ social contagion concerns (i.e., fear of being misclassified as gay/lesbian) relate to decreased behavioral intentions to help victims of bullying, by increasing negative attitudes towards lesbians and gay men. Study 2 (N = 230) further explored if inclusive identity representations (i.e., one-group or dual-identity) were related to decreased concerns of social contagion, thereby increasing adolescents’ assertive behavioral intentions. Results (partially) confirmed both expected mediations: social contagion concerns were associated with decreased assertive behavioral intentions via increased negative attitudes towards lesbians and gay men (Study 1); one-group representations, but not dual-identity representations, were associated with more assertive behavioral intentions via decreased social contagion concerns (Study 2). These findings extended previous studies illustrating the underlying mechanisms through which social contagion concerns and common identity affect assertive bystanders’ behavioral intentions.